An Assessment of the Reliability and Factorial Validity of the Chinese Version of the Health Professional Education in Patient Safety Survey (H-PEPSS) - Chen, Lingling; Huang, Feifei; Yuan, Xiaohuan; Song, Jihong; Chen, Linghui (Frontiers in Psychology, 2019)
Background: A nursing student’s reflection on their knowledge and competence in patient safety may prepare them to provide safer care in certain circumstances. The Health Professional Education in Patient Safety Survey (H-PEPSS) is a validated tool for assessing the perceptions of nursing students with regards to competence in patient safety competence. The H-PEPSS is widely used internationally but is not available in Chinese. Objectives: This study aimed to translate the H-PEPSS into Chinese and test its psychometric properties among Chinese undergraduate nursing students. Design: This was a cross-sectional online survey that was conducted in 2018. Settings: Seven nursing schools in North, East, Northeast, Central, Southwest, South, and Northwest China. Participants: A total of 732 final-year undergraduate nursing students were recruited by convenience sampling. Methods: Translation was conducted rigorously in accordance with an adapted version of Brislin’s translation model. Psychometric evaluation was conducted by incorporating classical test theory and item response theory (IRT) analysis. Results: The Chinese version of the H-PEPSS (both the classroom and clinical practice versions) achieved a Cronbach’s α, marginal reliability and 2-week test-retest reliability of >0.85. A six-factor solution explaining 81.49% and 82.32% of the total variance was obtained for the classroom and clinical practice versions, respectively. This was further validated by confirmatory factor analysis. IRT analysis showed that the scale offers a broad range of information on patient safety competence and discriminates efficiently between patients with high and low levels of competence in patient safety. Conclusions: The Chinese version of the H-PEPSS is a reliable and valid instrument that is capable of evaluating competence in patient safety perceived by undergraduate nursing students. In addition, the survey may also be used to evaluate gaps in classroom knowledge and clinical competence, and to offer valid data for designing or tailoring new education strategies.